Manajemen Kurikulum Pendidikan Agama Islam dan Budi Pekerti Jenjang SMA Bermuatan Keilmuan Integrasi Interkoneksi - Wiji Hidayati (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2016)
Islamic education and character education within the 2013 Curriculum at Senior High School in Indonesia are included in group A topics which is considered as compulsory. The central government has formulated purposes, learning outcome competence, core competence as well as basic competence of those two topics. Thus, it requires high-quality management to achieve the standards. However, in reality, Islamic education and character education teachers, particularly at State Senior High School I Pakem, Yoyakarta, are rarely aware of this scientific content in relation to management activities. It is admitted there that management activity is, in fact, teacher obligation yet it is often regarded merely as routine. This research, which is aimed at describing curriculum management on Islamic education and character education with integration –interconnection scientific content at Senior High School, is a field study using qualitative approach. The subjects are Islamic education and character education teachers at State Senior High School I Pakem Yogyakarta while the object is the curriculum management of Islamic education and character education of Senior High School class X, XI and XII. Data were gathered using observation, interview and documentation which are then analyzed based on Matthew B. Miles and A. Michael Huberman. Flow model was used as data analysis including three elements namely, data gathering which was done along with data reduction using classification, topic concentration and generalization, abstraction and rough data transformation; data analysis which comprises data display, information arrangement and conclusion or data verification under the topic of curriculum management of Islamic education and character education at Senior High School particularly on planning, organizing, actuating, and controlling phase related to integration-interconnection among bayani, irfani and burhani. The result shows that, at class X, there is core topic under the themes of ”Living virtuous life” and ”Managing wakaf truthfully”, while at class XI, the core topic is ”Hi Moslem warriors, wake up and rise!”, whereas at class XII, the core topic is ”Worshiping spiritfully by believing on the doomsday”.